An exploration of the esoteric and music in the novels and short stories of Julio Cortázar - Mc Donagh, Helen (Trinity College (Dublin, Ireland). Department of Hispanic Studies, 2014)
Far from being polar opposites, esoteric elements and musical motifs complement one another in enriching our construal of the prose fiction of Julio Cortazar. Although numerous studies deal with discrete esoteric themes in Cortazar’s works, none marries these motifs with his treatment of music therein. In the current study, I aim to examine Cortazar’s novels diachronically, focussing predominantly on the arcane. I also cast a glance at the influence of music, specifically in the form of tango, classical music and, to a greater degree, jazz throughout his work.
Keywords: Hispanic Studies, Ph.D.; Ph.D. Trinity College Dublin